THE INNOVATIVE APPROACH TO IMPROVE STUDENTS' ARABIC LANGUAGE PROFICIENCY: A STUDY AT AN ISLAMIC BOARDING SCHOOL - Luthfi, Muh Khairul (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRAKKemampuan berbahasa Arab yang baik sangat diperlukan untuk memahami dan menginterprestasikan teks-teks suci seperti Al-Qur'an dan Hadis. Namun, dalam praktiknya, tidak semua siswa-siswi di pondok pesantren memiliki kemampuan berbahasa Arab yang memadai. Dengan pendekatan inovatif, siswa di pondok pesantren diharapkan lebih termotivasi dan lebih terlibat dalam pembelajaran bahasa Arab, yang pada akhirnya dapat meningkatkan pemahamannya tentang agama Islam dan memungkinkan untuk berkontribusi lebih aktif dalam masyarakat muslim secara keseluruhan. Metode penelitian yang digunakan deskriptif kualitatif postpositivisme, Sampel atau informan penelitian ini adalah 1 orang guru kelas bahasa Arab dan 30 orang siswa kelas 8 Pondok Pesantren. Hasil dalam penelitian ini ialah Listening Comprehension sekitar 80%, Speaking Proficiency 65%, Reading Comprehension 85%, Writing Proficiency 80%, dan Vocabulary/Grammar 90% dalam bahasa Arab, hal ini menujukkan bahwa adanya perubahan pada pembelajaran bahasa Arab santri di pondok pesantren melalui pembelajaran inovatif.Kata Kunci: Inovatif, Kemamouan Bahasa Arab,Pondok Pesantren ABSTRACTGood Arabic language skills are needed to understand and interpret sacred texts such as the Qur'an and Hadith. However, in practice, not all students in boarding schools have adequate Arabic language skills. With an innovative approach, students in Islamic boarding schools are expected to be more motivated and more engaged in learning Arabic, which in turn can improve their understanding of Islam and enable them to contribute more actively in the Muslim community as a whole. The research method used was descriptive qualitative postpositivism, the samples or informants of this research were 1 Arabic class teacher and 30 students of grade 8 of the Islamic boarding school. The results in this study are Listening Comprehension around 80%, Speaking Proficiency 65%, Reading Comprehension 85%, Writing Proficiency 80%, and Vocabulary/Grammar 90% in Arabic, this shows that there is a change in the students' Arabic language learning at the boarding school through innovative learning.Keywords: Arabic Language Proficiency, Innovative, Islamic Boarding School